Is Job productivity Determined by Incentives, Workloads, and Job Satisfaction? - Ikramina Larasati Hazrati Havidz; Novitasari .; M. Havidz Aima; Hernawati W. Retno Wiratih (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Most of the retail industry at current time tend to utilize the advance technology adoption to enhance their job productivity. Advance technology utilization might lead to business competition in the retail industry. Thus, the study would like to analyse the determinants of job productivity at PT XYZ Department Store. The study aims to framed out the determinants factor of job productivity and to find out the mediating role of job satisfaction on incentives and workloads to job productivity. The study applies non-probability sampling method with 145 respondents collected. Smart-PLS is the statistical tools that is used to analyse the collected data. The proposed hypotheses in the study are all accepted. The results of this study prove that Incentives and Workloads have a positive and significant effect on Job Satisfaction; Incentives and Job Satisfaction have a positive and significant effect on Job Productivity; Workload has a negative and significant effect on Job Productivity; Job satisfaction plays a partial mediator role from incentives to Job Productivity; Last but not least, Job Satisfaction plays a full mediator role from Workload to Job Productivity